Meningkatkan Aktivitas Belajar Pendidikan Agama Islam pada Materi Akhlak Melalui Model Pembelajaran Talking Stick: Telaah Deskriptif di MA Al-Ihsan Kalikejambon Tembelang Jombang - Khoirul Huda; Zainul Abidin; Umi Nadhifah (Sumbula: Jurnal Studi Keagamaan, Sosial dan Budaya, 2025)
This study aims to determine the level of learning activity of Islamic Religious Education on Morals Material through the Talking Stick learning model at MA Al-Ihsan Kalikejambon Tembelang Jombang. This research is a qualitative study with a descriptive qualitative approach. The data collection method uses observation, interview and documentation methods. While the data analysis method uses the Miles and Huberman model, namely through data collection, data reduction, data presentation and drawing conclusions / verification. The findings obtained from the results of observations and interviews are that in MA Al-Ihsan Kalikejambon Tembelang Jombang itself, the Talking Stick learning method has not been applied to Islamic Religious Education learning on Moral material, this makes student learning activities still low and less active. Then after the Talking Stick learning model was applied to moral material in one of the X IPA 1 classes of MA Al-Ihsan Kalikejambon Tembelang Jombang, student learning activities increased although not significantly. Keywords: Learning Activities, Talking Stick Learning Model